Assessment of sleep in children with periodic fever, aphthous stomatitis, pharyngitis, and adenitis syndrome - Nalbantoğlu, Ayşin; Nalbantoğlu, Burçin (The Turkish Journal of Pediatrics, 2021)
Background. Periodic fever, aphthous stomatitis, pharyngitis and adenitis (PFAPA) syndrome is the most common cause of periodic fever in childhood. This study aimed to investigate sleep patterns and possible factors that are associated with sleep disturbances among children with PFAPA syndrome. Methods. Sixty-two patients with PFAPA and 68 age and sex matched healthy controls were enrolled in the study. Patients who had an attack during the former 2 weeks were not included. Demographic and anthropometric data, duration of fever episodes, laboratory results, and clinical manifestations of patients were recorded. The Children`s Sleep Habits Questionnaire was administered. Results. The total sleep scores of patients with PFAPA were significantly higher than the control group (49.6 ± 10.7 vs. 38.3 ± 7.5, p = 0.002 ). Children with PFAPA had significantly higher scores regarding sleep-onset delay, sleep anxiety and night wakening (p=0.003, p=0.007, and p=0.014, respectively). Total sleep durations were similar between children with PFAPA and the control group. There was a significant positive correlation between the total sleep score and disease duration (r=0.425, p=0.002). Also there was a significant positive correlation between disease duration and sleep onset delay (r=0.561, p < 0.001) and night wakening (r=0.327, p=0.003). Conclusion. This study showed for the first time that patients with PFAPA have significantly disturbed sleep when compared to otherwise normal children. This study emphasized the need to assess sleep problems in children with PFAPA.